1986
DOI: 10.1203/00006450-198605000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Human and Bovine Milk: Comparison of Ganglioside Composition and Enterotoxin- Inhibitory Activity

Abstract: ABSTRACT. Milk gangliosides inhibit Vibrio cholerae enterotoxin and Escherichia coli heat-labile enterotoxin. Human milk gangliosides showed considerably higher enterotoxin-inhibitory activity compared to bovine and formula milk gangliosides as measured in vitro by enzymelinked immunosorbent assay and in vivo in rabbit small bowel loops. While gangliosides from less than 1 ml human milk inhibited 0.1 pg choleratoxin in vitro and in vivo, five to 10 times higher amounts of bovine milk gangliosides were necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 27 publications
6
71
1
Order By: Relevance
“…They are glycolipids composed of a small oligosaccharide chain consisting of at least one sialic acid sugar, linked to a lipid ceramide [9]. The level of total gangliosides in both human and bovine milk is c. 11 pglml, but formula feeds contain about half this concentration [7]; processing of bovine milk for infant formula removes the fat globule membrane [ lo]. The composition of individual gangliosides is also different in the milks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are glycolipids composed of a small oligosaccharide chain consisting of at least one sialic acid sugar, linked to a lipid ceramide [9]. The level of total gangliosides in both human and bovine milk is c. 11 pglml, but formula feeds contain about half this concentration [7]; processing of bovine milk for infant formula removes the fat globule membrane [ lo]. The composition of individual gangliosides is also different in the milks.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of individual gangliosides is also different in the milks. In human milk, GM3 (monosialo-; 74% of total gangliosiues) is at a higher concentration than GM2 (monosialo-; 2%) and GMl (monosialo-; O.l%), while in bovine milk GM3 constitutes only a minor component (3%); all have a single sialyl-lactose structure associated with them [7,111. The major ganglioside found in bovine milk is GD3 (disialo-; 80% ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the ganglioside GM1 blocks adhesion of V. cholerae and binds to the E. coli, V. cholerae and C. jejuni enterotoxins Otnaess et al 1983;Ruiz-Palacios et al 1983). Respiratory syncytial virus (Laegreid et al 1986) and hepatitis A virus (Zajac et al 1991) are each neutralized by a different milk glycoprotein.…”
Section: Lactoferrinmentioning
confidence: 99%
“…Studies have shown that gangliosides exhibit antimicrobial, antiviral, and enterotoxininhibiting properties (Agarwal and Neter, 1971;Tsui et al, 1989;Hayashi and Niwayama, 1993;Laegreid et al, 1986;Boykins et al, 1994Boykins et al, , 1995Kawakami, 1997;Portelli et al, 1998;Rueda et al, 1998a, b). Gangliosides are sialic-acid-containing glycosphingolipids found ubiquitously in cell membranes of higher animals.…”
Section: Introductionmentioning
confidence: 96%
“…The ganglioside composition of milk fat from mammalian species can di!er markedly (Plantz and Patton, 1973;Laegreid et al, 1986;Puente et al, 1996), and the ganglioside content of a given milk can change during lactation (Takamizawa et al, 1986a;Puente et al, 1994Puente et al, , 1995Rueda et al, 1995;Pan and Izumi, 1999). Unique gangliosides have been found in buttermilk (Huang, 1973;Takamizawa et al, 1986b;Ren et al, 1992), suggesting cultured dairy products may show other variations.…”
Section: Introductionmentioning
confidence: 98%